Influencia del transtorno depresivo y ansiedad generalizada (TAG) en la presentación de síntomas gastrointestinales en pacientes del Hospital Manual Ignacio Monteros de la ciudad de Loja (IEES Loja), en el servicio de consulta externa de psiquiatría, en el período diciembre 2012-junio 2013 - Narváez Espinoza, Betty Alexandra (2014)
This study shows that the relationship between depression and generalized anxiety for the presentation of gastrointestinal symptoms is the collection of information is made based on the medical records of patients seen in the period specified. In depression there mood, temporary or permanent disorder characterized by feelings of depression, unhappiness and guilt, causing a total or partial inability to enjoy the events of everyday life. Generalized anxiety disorder characterized by a persistent pattern of concern and anxiety with respect to a variety of events or activities where symptom should extend at least 6 months , are two currently pathology related to many somatization diseases. The age group with the highest percentage was between 31-40 years, among the most common gastrointestinal complaints vomiting, nausea, constipation, abdominal pain and bloating are the lowest percentages. The evolution of symptoms in most patients was chronic and not responding favorably to treatment of gastrointestinal discomfort. There are many reasons why general psychiatry should be interested somatization and hypochondria, as they are causes of consultation in primary care, after controlling depression and anxiety.